Nutritional status and nutrient intake from complementary foods among breastfed children in Purworejo District, Central Java, Indonesia - Endang Dewi Lestari; T Ninuk S Hartini; M Hakimi; A Surjono (Indonesian Pediatric Society, 2005)
Background The growth rate of Indonesian infants beyond sixmonths of age declines compared with that of the internationalreference population.Objective This study aimed to describe the pattern of nutritionalstatus among breastfed children and their intake of energy, pro-tein, and zinc from complementary foods in Purworejo District, Cen-tral Java, Indonesia.Methods The study was a cross sectional survey drawing breastfedchildren under 24 months old from a well-defined population. Chil-dren with a history of prematurity or low birth weight were excluded.Anthropometrical measurements were collected. Intake of comple-mentary food was assessed using 24-hour recall. Analysis of nu-tritional intake was only performed in 11-23 month-old children.Results Of 577 children enrolled, the prevalence of underweight,stunting, and wasting were 8.1%, 8.8%, and 4.6%, respectively.The prevalence of undernutrition increased with age. There wasno association between frequency of breastfeeding during 24 hoursin the second year of life and the nutritional status. The averageintake of energy, protein, and zinc from complementary foods wasvery low i.e., 30%, 45%, and 5% of the Indonesian recommendeddietary allowance (RDA), respectively.Conclusion The prevalence of undernutrition in breastfed chil-dren increases with age. The breastfed children beyond 11 monthsof age in Purworejo District need sufficient density of nutrients fromcomplementary foods.